2019
DOI: 10.1007/s11111-019-00329-2
|View full text |Cite
|
Sign up to set email alerts
|

Missing millions: undercounting urbanization in India

Abstract: The measurement and characterization of urbanization crucially depends upon defining what counts as urban. The government of India estimates that only 31% of the population is urban. We show that this is an artifact of the definition of urbanity and an underestimate of the level of urbanization in India. We use a random forest-based model to create a high-resolution (~100 m) population grid from district-level data available from the Indian Census for 2001 and 2011, a novel application of such methods to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, due to the poor public transit infrastructure in India's urban regions, inhabitants opt for private transportation, which has led to massive automobile emissions that contribute to environmental deterioration. Consequently, urbanization in India causes environmental pollution and worsens population health over the long haul (57). As per the IQAir report, India's air quality is unhealthy; the most current statistics show that the country's annual mean concentration exceeds the recommended level of 10 g/m 3 (58).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the poor public transit infrastructure in India's urban regions, inhabitants opt for private transportation, which has led to massive automobile emissions that contribute to environmental deterioration. Consequently, urbanization in India causes environmental pollution and worsens population health over the long haul (57). As per the IQAir report, India's air quality is unhealthy; the most current statistics show that the country's annual mean concentration exceeds the recommended level of 10 g/m 3 (58).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid urbanisation in the near future is estimated to add about 416 million dwellers by 2050. Other studies reported and estimated that the urban population is about 12% more than the official statistics by the Government of India in Census 2011 (Onda et al , 2019; Van Duijne, 2019). While there is no exact data for the number of people engaged in urban agriculture in India, a study by Paschapur and Bhat (2020) revealed that about 65% of produce in urban markets comes from peri-urban production.…”
Section: Methodsmentioning
confidence: 96%
“…The DEGURBA draws on two harmonised EU datasets: the Global Human Settlement Population (GHS-POP) and GHS Settlement Model (SMOD), which are classified based on population size, population counts and built-up area densities. Whilst the classification of urban areas using standardised geographies and urban definitions does facilitate international statistical comparisons, the rigid classification criteria has been controversial [9,10]. More generally and related to the above, smaller urban areas are more difficult to classify than larger urban areas using rigid criteria.…”
Section: Introductionmentioning
confidence: 99%